1988
DOI: 10.1002/mrm.1910080210
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative NMR measurements of hippocampal atrophy in Alzheimer's disease

Abstract: Nuclear magnetic resonance (NMR) imaging was employed to study 10 patients with Alzheimer's disease (AD) and seven healthy elderly control subjects. Coronal sections were used to make volumetric measurements of the hippocampus, ventricles, subarachnoid space, and brain parenchyma. The hippocampal volume (normalized relative to the size of the lenticular nucleus) was reduced by 40% in the AD group compared to the controls, with no overlap between the two groups. Overall measures of brain atrophy and ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
143
1
9

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(169 citation statements)
references
References 28 publications
14
143
1
9
Order By: Relevance
“…Based upon what is known from patient studies (e.g. [17,33,38,39]), it was expected that reductions in total brain volume would be related to a decline in performance on global cognitive tests measuring speed of mental processing, whereas atrophy of limbic structures (hippocampus, parahippocampal gyrus and mamillary bodies; and third ventricle as an index for the dorsomedial thalamus [19]) would be specifically associated with a deterioration on memory tests. We found a somewhat different pattern.…”
Section: Relation Between Brain Volumes and Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Based upon what is known from patient studies (e.g. [17,33,38,39]), it was expected that reductions in total brain volume would be related to a decline in performance on global cognitive tests measuring speed of mental processing, whereas atrophy of limbic structures (hippocampus, parahippocampal gyrus and mamillary bodies; and third ventricle as an index for the dorsomedial thalamus [19]) would be specifically associated with a deterioration on memory tests. We found a somewhat different pattern.…”
Section: Relation Between Brain Volumes and Cognitive Performancementioning
confidence: 99%
“…Alzheimer's disease and Korsakoff's syndrome) have demonstrated that damage to specific brain structures is indeed related to deterioration of cognitive functions. In these studies memory impairment is often associated with atrophy of limbic structures (including hippocampus, parahippocampal gyrus [17], thalamus [38], or third ventricle [39], and mamillary bodies [36]), whereas global cognitive deficits such as slower mental processing is related to more general cerebral atrophy [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional MRI studies have shown that AD patients have significantly greater ERC and hippocampal atrophy than cognitively normal (CN) subjects [9,21,26,48,57]. Longitudinal MRI studies have suggested that the rates of ERC and hippocampal atrophy may be useful in predicting AD before the onset of clinical symptoms and in assessing the potential usefulness of pharmacological interventions in treatment trials [10,22,24,27,43].…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal volumes, measured in-vivo, using quantitative 3D MRI have been investigated in many aging and dementia related studies (Seab et al, 1988, Jack et al, 1992, Juottonen et al, 1999, Laakso et al, 2000, Sencakova et al, 2001, Du et al, 2002. As Alzheimer's disease (AD) and vascular dementia (VaD) are two common types of dementia, volumetric measures of hippocampus and other medial temporal lobe structures in both disease groups are often compared to non-demented controls.…”
Section: Introductionmentioning
confidence: 99%